Optimalisasi Peran Posyandu Melalui Pemantauan Pertumbuhan dan Edukasi Gizi sebagai Strategi Pencegahan dan Deteksi Dini Stunting di Desa Nagreg, Banten (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Stunting is a chronic nutritional problem that affects children's growth and development and remains a major public health challenge. Posyandu plays a strategic role in the prevention and early detection of stunting through community-based basic health services. This community service activity aims to optimize the role of Posyandu as a strategy for preventing and detecting stunting early in Nagreg Village, Banten. The methods used include anthropometric measurements of children aged 0–59 months and health education on nutrition for parents and Posyandu cadres. Data analysis was conducted descriptively based on age groups. The results show that out of 32 children examined, 37.5% showed indications of stunting risk. This finding suggests that the integration of growth monitoring and nutrition education at Posyandu has the potential to be an effective strategy for the prevention and early detection of stunting, as well as to support the improvement of children's health quality. This activity also enhances parents' and Posyandu cadres' understanding of the importance of monitoring nutritional status to prevent stunting more effectively.